Development of Medical Wellness-Based Health Tourism in Indonesia: Case Study of Traditional Medicine and Melukat Ritual in Bali - Dewi, Riskha Dora Candra (CV. Strata Persada Academia, 2025)
Health tourism has emerged as a rapidly growing global economic sector, with countries competing to attract tourists seeking holistic health services. With its rich natural and cultural resources, Indonesia has significant potential to establish itself as a leading destination in this field. This study explores the potential for developing medical wellness-based health tourism in Bali, focusing on traditional medicine and the Melukat ritual. Utilizing a qualitative approach and a literature review methodology, this study highlights Bali's unique advantages, including internationally recognized traditional healing practices and the culturally rich Melukat ritual, which integrates physical, mental, and spiritual health benefits. This study also finds that melukat has gained recognition not only for its therapeutic effects on mental well-being but also as a unique interfaith tourism trend. By promoting this ritual within the framework of medical wellness tourism, Bali can leverage its cultural assets to attract a premium segment of health-conscious tourists while contributing to the preservation of local traditions. This study provides actionable recommendations for policymakers and stakeholders, contributing to Bali's positioning as a premier medical wellness tourism destination. By integrating traditional medicine and Melukat rituals into tourism packages, Bali can attract health-conscious tourists, preserve its cultural heritage, and support local economic growth.